THE LITHOTYPE DETERMINATION IN THE LOWER CARBON ROCKS OF THE LOKHVITSKA STRUCTURAL TECTONIC ZONE (THE DNIEPER-DONETS DEPRESSION) ON THE BASIS OF RELATION PП=F(KП) - KURHANSKYI, V.; RIABUKHA, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
The detailed complex petrophysical investigations of the Lower Carbon rocks of the Loxvitska structurally-tectonic zone (the Dnieper-Donets depression, Ukraine) have been made. The probability to determine lithotype of rocks on the basis of relation Рп=f(Кп) is indicating.